Complex prosthetic rehabilitation of a patient with amelogenesis imperfecta with digital workflows - Klaudia Lipták; Laura Lipták; Tamás Déri; Péter Hermann (Hungarian Dental Association, 2023)
Introduction: Amelogenesis imperfecta (AI) is a diverse collection of inherited diseases that show quantitative and qualitative defects in tooth enamel in the absence of systemic manifestations. Patients with AI often have open bite, which also requires complex care. In the final dental treatment, the focus should be on the preparation of indirect restorations, so early detection and care can be key factors for long-term success, as poor-quality enamel can be more easily attacked by caries. Case report: A 15-year-old young female patient presented to the Department of Prosthodontics of Semmelweis University in 2022 because of her worn down teeth due to amelogenesis imperfecta. The patient also had open bite. During the intraoral examination, reduced enamel was detected on all teeth, with partial enamel breakdown, exposing the dentin. Following the current professional recommendations, we planned monolithic zirconia crowns and splints as well as bridges to correct the tooth gaps on the upper and lower arches. In the first phase of the treatment, we increased the occlusal vertical dimension using a gothic arch tracer and digital face bow (Zebris for Ceramill). The impressions were taken by the 3Shape Trios 3 Pod, making it more comfortable for the patient and easier to copy accurately the increased occlusal vertical dimension from the temporary restoration to the final restoration. Due to the damaged tooth structure, for the final cementation resin modified glass ionomer was used. Protecting the monolithic zirconia restorations, the temporomandibular joint and the muscles, a Michigan-splint was created for the patient. Summary: For patients with AI, the appearance of the teeth can cause psychological and functional problems, so the goal of every treatment plan is restoration, and regular follow-up. Maintaining proper oral hygiene is also essential for patients with AI, and according to the literature, treatment with indirect restorations increases success compared to direct treatments.